TEACHING PROFESSIONALS ISSUES OF THE PROCESS OF THE SUBJECT MATHEMATICS EDUCATION. - Vega Héctor, Nancy; González Medina, Marielys (Atenas, 2014)
Students in Special Education degree program must meet the challenge of preparing for professional problem solving teaching from academic components, labor and research, this function has a special significance in the educational professional performance. The objective of the research is to characterize the solution of professional problems in the direction of teaching teaching-learning process of the course Mathematics Education. It is a methodological tool that is inserted into the Discipline Teaching Specifications for teacher training in special education.